2017
DOI: 10.1105/tpc.17.00037
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of the DNA Replication Timing Program during Mitotic S Phase in Maize (Zea mays) Root Tips

Abstract: All plants and animals must replicate their DNA, using a regulated process to ensure that their genomes are completely and accurately replicated. DNA replication timing programs have been extensively studied in yeast and animal systems, but much less is known about the replication programs of plants. We report a novel adaptation of the "Repli-seq" assay for use in intact root tips of maize (Zea mays) that includes several different cell lineages and present whole-genome replication timing profiles from cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 149 publications
(258 reference statements)
6
44
0
Order By: Relevance
“…In middle S phase, replication was almost evenly dispersed along the entire chromosomes and only slightly increased in the interstitial regions of chromosome arms. These findings confirmed the recent results made in Arabidopsis and maize obtained by Repli-seq analysis and corresponded to the gene density of their chromosome profiles (Wear et al , 2017, Zynda et al , 2017; Concia et al , 2018). Kwasniewska et al (2018) showed that terminal parts of barley chromosomes replicated in early S phase, whole chromosomes were covered with EdU signal at middle S phase and centromeric parts of chromosomes were replicated in late S phase.…”
Section: Discussionsupporting
confidence: 91%
“…In middle S phase, replication was almost evenly dispersed along the entire chromosomes and only slightly increased in the interstitial regions of chromosome arms. These findings confirmed the recent results made in Arabidopsis and maize obtained by Repli-seq analysis and corresponded to the gene density of their chromosome profiles (Wear et al , 2017, Zynda et al , 2017; Concia et al , 2018). Kwasniewska et al (2018) showed that terminal parts of barley chromosomes replicated in early S phase, whole chromosomes were covered with EdU signal at middle S phase and centromeric parts of chromosomes were replicated in late S phase.…”
Section: Discussionsupporting
confidence: 91%
“…As a consequence, it is not known if the conclusions from these experiments accurately describe DNA replication under normal conditions. To address this concern, we developed a new functional assay by combining brief labeling with 5-ethynyl-2'-deoxy-uridine (EdU) (Bass et al, 2015;Ramachandran and Henikoff, 2016;Dvořáčková et al, 2018;Macheret and Halazonetis, 2018;Tubbs et al, 2018;Macheret and Halazonetis, 2019) with flow sorting (Wear et al, 2016;Wear et al, 2017;Concia et al, 2018) to isolate nuclei in which replication has just begun, so that label is incorporated close to the points of initiation. This was followed by immunoprecipitation and characterization of the labeled DNA.…”
Section: Introductionmentioning
confidence: 99%
“…2f). DNA replication initiation regions (Wear et al 2017) were associated with both group A and group B pan-And-CNSs (Fig. 2g).…”
Section: Conserved Non-coding Sequence Comprised a Wide Range Of Funcmentioning
confidence: 98%
“…The DNA duplication signals files were downloaded from the original publication (Wear et al 2017). And the maize reference V3 coordinates were uplifted to V4 coordinates using CrossMap v0.2.8 (Zhao et al 2014) and the chain file released from ensembl website.…”
Section: Overlapping Cns With Dna Duplication Initial Regionsmentioning
confidence: 99%